Biocompatible nanocomposite cryogels with improved mechanical properties based on polyvinyl alcohol and carbon nanotubes for cardiovascular applications - Rezvova, Maria A.; Glushkova, Tatiana V.; Klyshnikov, Kirill Yu; Pykin, Alexey L.; Tkachenko, Tatiana B.; Akentieva, Tatiana N.; Kostyunin, Alexander E.; Onishchenko, Pavel S.; Borisova, Natalia N.; Fokeeva, Marina P.; Matveeva, Vera G.; Senokosova, Evgenia A.; et al. (Frontiers in Bioengineering and Biotechnology, 2025)
The unique properties of hydrogels have enabled their widespread use in various biomedical applications, including heart valve and blood vessel replacements. However, their current applications are limited by poor mechanical properties, including low strength, susceptibility to plastic deformation, and inadequate wear resistance, which are critical for load-bearing tissue replacements. Nanocomposite cryogels composed of polyvinyl alcohol and carbon nanotubes prepared using a DMSO/H2O solvent mixture, present a promising solution to address these limitations. Addition of nanoparticles up to 0.5% of the polymer mass showed a remarkable 59% increase in mechanical strength compared to single component cryogels. The reinforcement effect was also pronounced in strain hardening at large deformations. CNTs addition also enhanced the adhesion of Ea.hy 926 cells. However, the overall cell coverage on the cryogel surface was lower compared to control culture plastic, suggesting selective adhesion behavior. Comprehensive hemocompatibility testing showed minimal adsorption of protein molecules such as albumin and fibrinogen and no platelet adhesion when exposed to platelet rich plasma. Post contact platelet aggregation was same as untreated plasma. The studied materials also elicited minimal inflammatory response and no calcification unlike polytetrafluoroethylene which is clinically used, further proving biocompatibility. These findings suggest that PVA-based nanocomposite cryogels synthesized with dispersed CNTs hold significant promise for applications in cardiovascular surgery, particularly in the development of mechanically robust and biocompatible vascular grafts and heart valve prostheses.